Effects of Task and Presentation Modality in Detection Response Tasks - Vilimek, Roman; Schäfer, Juliane; Keinath, Andreas (Engineering Psychology and Cognitive Ergonomics. Understanding Human Cognition, 2013)
To assess driver distraction adequately, cognitive workload measurement techniques are necessary that can be used as part of standard in-vehicle testing procedures. Detection response tasks (DRTs) are a simple and effective way of assessing workload. However, as DRTs require cognitive resources themselves, interferences between task modality and DRT modality are possible. In this study, DRT stimuli (auditory, visual, tactile) are varied systematically with secondary task presentation modality (auditory, visual, or purely cognitive tasks). The aim is to infer if different DRT variants remain sensitive to changes in workload even if primary and secondary task convey information using the same presentation modality, thus making resource conflicts likely. Results show that all DRTs successfully discriminate between high and low workload levels in terms of reaction time independent of DRT presentation modality. Differences in discriminability can be found in hit rate measurement.